Impact of Rear Slope Variation on Rubble Mound Breakwater Stability Under Seismic Loading - Morabit, Abdelmajid; El Ghoulbzouri, Abdelouafi (Civil Engineering Journal, 2024)
This study aims to enhance the seismic stability of rubble mound breakwaters, crucial maritime structures, by examining how variations in the rear slope angle affect their response to seismic loads. Utilizing the Plaxis 2D software, a finite element method was employed to simulate the behavior of a conventional rubble mound breakwater under different seismic conditions. The analysis considered three different rear slope angles and subjected each to various seismic loads characterized by differing amplitudes and frequencies. Our findings indicate that the rear slope inclination significantly influences the seismic response of the breakwaters, notably affecting the displacements and deformations within the structure. The most optimal angle of inclination was identified, which minimized the seismic-induced deformations, thereby potentially improving the structural integrity and longevity of these maritime defenses. This investigation not only provides valuable insights into the design of more resilient maritime structures but also introduces an approach to optimize breakwater design for better performance under seismic conditions, marking a notable improvement in the field of maritime engineering. Doi: 10.28991/CEJ-SP2024-010-08 Full Text: PDF